REBELLION OF MAIN CHARACTER IN LAUREN DESTEFANO’S WITHER - Nadiah Nur Fatimah; Linusia Marsih (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
This study aims to reveal rebellion of main character in Lauren DeStefano’s Wither. The discussion is focused on Rhine’s rebellion which is trigerred by dystopian-life happened in the society. In revealing the rebellion reflected in the novel, Mercuse’s theory of rebellion and Millner’s theory of dystopian-life are applied. The research method applied in this study is descriptive qualitative with intrinsic and extrinsic approaches. Based on the analysis, the writer finds out that among the nine dystopian society characteristics, the writer has found five characteristics that are reflected in Wither, namely the society is an illusion of utopia world; the natural world is being a banished and distrusted world; perception under constant surveillance; fear ot the outside world; and information, independent thought, and freedom are restricted. In addition, the analysis of the main character’s rebellion shows that the rebellion happens as the impact of dystopian society faced by the main character. Rhine’s rebellion is done in four ways – having intention to escape from Linden’s house, refusing to be consummated by her husband, having relationship with Gabriel, and escaping. The reasons of Rhine’s rebellion are wanting to be reunited with her brother and wanting to have freedom. After doing the analysis, the writer finds out that science and technology should be developed for human’s better condition. Science and technology must not be expected beyond God’s power. When science and technology is developed without consideration in terms of humanity, it will result in chaosness.